A comparison of a 4% modified fluid gelatin and a 6% hydroxyethyl starch on haemodilution colloid osmotic pressure haemostasis and renal parameters in healthy ponies - Lyle, Catriona H. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.